Penicillium marneffei mesenteric lymphadenitis in human immunodeficiency virus-infected children - Ukarapol N. (2014)
Disseminated P. marneffei infection is one of the common opportunistic infections seen in HIV-infected patients in Southeast Asia. We report 3 cases of HIV-infected children with mesenteric lymphadenitis presented with prolonged fever and abdominal pain. The first two patients were diagnosed as peritonitis and acute appendicitis prior to exploratory laparotomy. Operative findings revealed multiple enlarged mesenteric lymph nodes. Histopathologic findings of mesenteric lymph nodes biopsy were characteristic for P. marneffei infection. Mesenteric lymphadenitis in the last patient was diagnosed by abdominal ultrasound. All three cases had positive blood and bone marrow cultures for P. marneffei. These patients were treated with amphotericin B. Fever declined in 3-6 days. The first two patients survived but the last one subsequently died from underlying hemophilia A (GI bleeding). CONCLUSION: Acute mesenteric lymphadenitis can be one of the unusual manifestations caused by P. marneffei. Southeast Asia is an endemic area for P. marneffei and is severely affected by acquired immunodeficiency syndrome epidemic. Therefore, mesenteric lymphadenitis should be considered in HIV-infected persons who present with prolonged fever and abdominal pain.